2003
DOI: 10.1016/s0736-5748(03)00075-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical inhibitors of cyclin‐dependent kinases control proliferation, apoptosis and differentiation of oligodendroglial cells

Abstract: Since cyclin-dependent kinases (Cdks) and their endogenous inhibitors (Cdkis) play an essential role as regulators of cell cycle withdrawal and onset of differentiation within oligodendroglial cells, we assessed here the effects of exogenous chemical Cdk inhibitors (CKIs) on cultured rat cortical oligodendrocyte progenitor cells (OPCs). We showed that purine derivatives and especially roscovitine strongly inhibited OPCs proliferation. In the presence of mitogenic signals, roscovitine synergized with thyroid ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…To examine whether normal development of the heart depends on proliferation in the caudal mesoderm, we locally inhibited cell division in the caudal and inner mesoderm by exposure to Aminopurvalanol,21 dissolved with DiI. Exposure to Aminopurvanol disrupted proliferation within 3 hours, as reflected in an absence of BrdU-incorporation (Supplementary Data).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine whether normal development of the heart depends on proliferation in the caudal mesoderm, we locally inhibited cell division in the caudal and inner mesoderm by exposure to Aminopurvalanol,21 dissolved with DiI. Exposure to Aminopurvanol disrupted proliferation within 3 hours, as reflected in an absence of BrdU-incorporation (Supplementary Data).…”
Section: Resultsmentioning
confidence: 99%
“…As previously described, embryos were exposed to DiI and DiO (Molecular Probes) using a picospritzer (General Valve Corp.) and a micromanipulator with a pulled glass capillary tube 21. To inhibit proliferation, 100 μM of the cyclin-dependent kinase inhibitor Aminopurvalanol A21 (Alexis Biochemicals) was dissolved with the DiI, and administered locally. Bright-field and fluorescent photos were made immediately after labeling and during further culturing.…”
Section: Methodsmentioning
confidence: 99%
“…The pathways involved include those mediated by tyrosine kinases (Di Fulvio et al, 2000;Utoh et al, 2003;Martinez and Gomes, 2005), protein kinase C (PKC) (Petcoff and Platt, 1992;Phillips and Platt, 1994;Wagner et al, 2001;Alisi et al, 2004), mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) (Lin et al, 1997(Lin et al, , 1998(Lin et al, , 1999aDavis et al, 2000;Bergh et al, 2005), cyclin-dependent kinases (Barrera-Hernandez et al, 1999;Nguyen et al, 2003;Skirrow, 2003;Skirrow and Helbing, 2007), and phosphatidylinositol-3 kinase (PI3K) (Lei et al, 2004;Cao et al, 2005;. However, the precise target substrates, the location of phosphorylation sites, their integration into the TH signaling pathway, and functional roles in specific tissues remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies on apoptosis following growth factor withdrawal have suggested that the G 1 /S stages of the cell cycle may be apoptosis-insensitive stages while other stages do not provide such resistance (16,41). For example, arresting PC12 cells or primary postmitotic sympathetic neurons with the one of the G 1 /S blockers mimosine, ciclopirox, or deferoxamine suppresses apoptosis of these cells following serum or growth factor withdrawal, whereas arresting in other stages of the cell cycle does not suppress apoptosis (16).…”
mentioning
confidence: 99%